Globalisation vs Europeanisation A Human-centric Interaction - Bekemans, Léonce (Peter Lang International Academic Publishing Group, 2013)
The book offers an innovating, interdisciplinary analysis of the relation between globalisation and Europeanisation from a value-driven and human-centric perspective. The approach goes beyond the traditional analysis and applies the proposed conceptual framework to various interconnected policy fields and issues, crucial to Europe's future.